Unknown Renal Impairment: A Rare Case of Inhaled Tobramycin Induced Acute Kidney Injury in a Cystic Fibrosis Patient - Tyler Miller; Cristina Pastuch; Lisa Garavaglia; Kelley Gannon; Anthony Parravani (MDPI AG, 2021)
Acute kidney injury is a reversible medical condition commonly caused by nephrotoxic agents. The infrequency that a nebulized medication elicits a renal insult presents a rare diagnostic challenge. Within this case, we report a 57-year-old cystic fibrosis patient with chronic kidney disease (CKD) Stage G3b (baseline 1.5-1.6 mg/dL) who developed an acute kidney injury (AKI) with a serum creatinine elevation to 4.08 mg/dL and associated worsening vestibular dysfunction related to twice-daily nebulized tobramycin inhalation solution (TIS). The patient was found to have a tobramycin serum level of 4.2 μg/mL 2.5 h after TIS dosing, with elevation remaining present at 1.1 μg/mL 24 h after discontinuation of therapy. Laboratory values at one month continued to show elevated creatinine levels at 2.1 mg/dL, suggesting progression of his baseline CKD. This case supports the benefit of obtaining tobramycin serum levels and vestibular/audiology function testing when evaluating patients on chronic nebulized TIS who present with acute or chronic renal dysfunction. From these serum levels, adjustments to daily dosing, regular monitoring of tobramycin serum levels, or discontinuation of treatment should be made to prevent permanent renal damage in patients with CKD. Calculated Naranjo ADR Probability Scale: 9; Definite.